Effects of the invasive alien plant Lupinus polyphyllus on the plant communities in road verges of high nature value - Dániel-Ferreira, Juliana; Lennartsson, Tommy; Wissman, Jörgen; Knudsen, Carola; Eckstein, Lutz (Swedish University of Agricultural Sciences, 2024)
The aim of this publication was to explore the effects of the invasive alien plant Lupinus polyphyllus on the plant communities in road verges of high nature value (artrika vägkanter). The linked data was collected in 24 road verges, half of which were located in the county of Uppland. The other half were located in the counties of Värmland and Örebro. The 24 road verges were selected from the Swedish National Road Database (NVDB). In these sites, two types of 1 × 1 m plots were established. The first type was placed such that the dominating species was the invasive L. polyphyllus, and the second was placed as close as possible to the first one but such that the invasive was absent. This was done to ensure that the plant communities were as similar as possible before invasion. A plant inventory, including density and identity, of all plant species except for the true grasses (Poaceae) in the plots was performed. The litter depth was also recorded.
The study is a part of the research program TRIIAS (https://triekol.se/triias/).

Målet med denna publikation var att utforska effekterna av den invasiva främmande arten Lupinus polyphyllus på växtsamhällena i vägkanter med högt naturvärde (s.k. artrika vägkanter). Datainsamlingen skedde längs 24 vägkanter, hälften av dem belägna i Upplands län. Den andra halvan var belägen i Värmland och Örebro. De 24 vägkanterna valdes ut från den svenska nationella vägdatabasen (NVDB). På dessa platser etablerades två typer av 1 × 1 m provytor. Den första typen placerades så att den dominerande arten var den invasiva L. polyphyllus, och den andra placerades så nära den första som möjligt, men så att den invasiva växten saknades. Detta gjordes för att säkerställa att växtsamhällena var så likartade som möjligt innan invasionen. En växtinventering, inklusive täthet och identitet, av alla växtarter utom gräs (Poaceae) i rutorna utfördes. Förnans djup registrerades också.
Studien är den del av forskningsprojektet TRIIAS (https://triekol.se/triias/).
Effekter av den invasiva främmande växten Lupinus polyphyllus på växtsamhällen i artrika vägkanter
Keywords: INVASIVE SPECIES; COMMUNITY STRUCTURE; tracheophyte; kärlväxter; Transport networks; Transportnät; Lupinus polyphyllus; blomsterlupin; Tracheophyta; kärlväxter; Garden lupine; blomsterlupin; linear infrastructure habitats; linjära infrastrukturmiljöer; Natural Sciences; Naturvetenskap; Botany; Botanik; Ecology; Ekologi; Biota; Biologi och ekologi